Pickering Emulsions of Kaffir Lime Oil Stabilized by Modified Tapioca Starch: Impact of Particle Size Reduction Methods and Octenyl Succinic Anhydride Grafting - Kamboon, Nuttida; Thepwatee, Sukanya; Boonsith, Suthida (Applied Science and Engineering Progress, 2026)
The main challenges in using tapioca starch for pickering emulsions are its native micron-sized particles, which are too large to stabilize small oil droplets, and its highly hydrophilic nature, which limits its ability to balance oil-water interfaces. This study explores the modification of tapioca starch to encapsulate kaffir lime oil (KO) in pickering emulsions, emphasizing particle size reduction and surface functionalization. Methods included enzymatic hydrolysis (alpha-amylase, alpha-amylase with glucoamylase, and pullulanase), sulfuric acid hydrolysis, and ethanol precipitation. Ethanol precipitation emerged as the most effective, producing ultra-fine particles (96–150 nm) with superior emulsion stability. Surface analysis revealed that enzymatic treatments affected particle morphology, while ethanol precipitation formed the smallest, smoothest particles and the lowest crystallinity (8.4%), compared to sulfuric acid hydrolysis, which showed the highest crystallinity (37.7%). Surface functionalization with octenyl succinic anhydride (OSA) enhanced starch hydrophobicity, confirmed by Fourier-transform infrared (FT-IR) spectroscopy and increased water contact angles. Pickering emulsions prepared with ethanol-precipitated starch esterified with 5% OSA showed the highest stability. Incorporating medium-chain triglyceride (MCT) oil at a KO/MCT ratio of 0.4/0.8 further improved droplet size and emulsion stability. These findings highlight ethanol-precipitated and OSA-modified tapioca starch as an effective bio-surfactant for stabilizing Pickering emulsions, with potential for sustainable and high-value industrial applications.